PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDS MUHAMMADIYAH KECAMATAN MANDAU KABUPATEN BENGKALIS - ', Darmendra; Marhadi, Hendri; ', Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was held because the study results of IV grade student of SDS Muhammadiyah kecamatan Mandau kabupaten Bengkalis in socials learning were still lower than KKM. The students who achieved KKM were 10 students (40,00%) and who can’t achieved KKM were 15 students (60%). The purpose of this research was to increased capability of IV grade student of SDS Muhammadiyah Kecamatan Mandau Kabupaten Bengkalis in socials learning with applied the cooperative learning model with type make a match. The result of this research show that the total score of student activity were increase at cycle I from first meeting with score 10 (41,66%) as category minus become 13 (54,16%) at second meeting with category sufficient. On the cycle II, the total score of student activity were also increase from 19 (79,16%) with category good become 21 (91,66%) with category very good. The study result of student increased from initial value to daily test I were by average 63,2 become 80,4 with percentage until 27,2% dan increasing to daily test II become 86,8 with percentage until 37,3%. For the value of classical completness of study result of socials learning from all student just take percentage 40% (cycle I). After the model of cooperative learning make a match was implemented on the cycle II, the value of classical completness increased become 88%. Based on the result of this research can be conclused that application model of cooperative learning make a match can increased the study result in socials learning of IV grade student of SDS Muhammadiyah kecamatan Mandau Kabupaten Bengkalis. Key Words: Make A Match, Learning Outcomes Of Socials Learning